Alteration of photosynthetic pigments and antioxidant systems in tomato under drought with Tebuconazole and Hexaconazole applications - Arivalagan, Maruthaiya; Somasundaram, Ramamurthy (Journal of Scientific Agriculture, 2017)
Present investigation was focused on the response and regulation of the antioxidant defense system and photosynthetic pigment variation effect of two important fungicides or plant growth regulators Hexaconazole (HEX) and Tebuconazole (TBZ) on drought stressed tomato (Lycopersicon esculentum Mill.) plants. Drought stress was imposed for 30 Days after sowing (DAS) of tomato plant. The water was irrigated by 4 Days Interval Drought (DID) and the control plants were regularly irrigated. Triazole treatment like HEX at 15 mg L-1 and TBZ at 10 mg L-1 imposed on 30, 40 and 50 DAS. The plant samples were collected on 40, 50 and 60 DAS. The photosynthetic pigments like chlorophyll – a, chlorophyll – b and total chlorophyll were estimated. The drought stress reduced the photosynthetic pigments and increased the antioxidant contents and antioxidant enzymes activities. The combined drought stress with triazole treatments increased the photosynthetic pigments then reduced the ascorbic acid (AA), α-tocopherol, catalase (CAT), peroxidase (POX) and superoxide dismutase (SOD) activities, when compared to drought stressed plants. It can be concluded that the triazole treatment partially mitigated the adverse effects of drought stress in L. esculentum.